Pellegrini-Stieda syndrome - Salah Ben Elhend; Hassan Doulhousne; Redouane Rokhssi; Nabil Hamoune (PAMJ Clinical Medicine, 2020)

(untitled)
Pellegrini-Stieda syndrome is a post-traumatic ossification/calcification of the medial collateral ligament (MCL), adjacent to the margin of the internal femoral condyle. In the light of four observations of Pellegrini-Stieda syndrome and a review of the literature, we propose to present the different epidemiological, etiopathogenic, pathological and radiological aspects of this rare syndrome. The role of imaging investigations, particularly of MRI (magnetic resonance imaging), is highlighted. Treatment is often medical, but in some cases surgical excision with ligament repair may be necessary.